Mannose receptor independent uptake of transmembrane glycocluster immunostimulant TADM by macrophages - Eichin, Dominik; Rahkila, Jani; Li, Xiang-Guo; Ekambaram, Ramesh; Lassfolk, Robert; Leino, Reko; Savolainen, Johannes (Elsevier, 2025)
Triacedimannose (TADM) is a synthetic trivalent acetylated glycocluster comprising β-1,2-linked mannobioses that in humans induces TNF in vitro and in vivo. The purpose of this study was to analyze whether uptake of acetylated glycoclusters of such β-1,2-linked mannobioses by human macrophages is dependent on the mannose receptor (CD206) or if it is mediated by transmembrane activation. In mannose receptor blocking assays, monocyte-derived polarized macrophages were incubated with carbohydrate test-compounds and their binding to the mannose receptor was demonstrated as inhibition of FITC-Dextran binding. For 1H NMR spectroscopy, macrophages were incubated with TADM. The cells were collected at 6 and 24 h of incubation, centrifuged and washed twice with PBS. We found dose-dependent blocking of the mannose receptor in macrophage carbohydrate constructs containing free hydroxyl groups, but not by the trivalent acetylated glycocluster molecules. NMR spectroscopic analyses demonstrated that TADM was found in washed cellular pellets after 6-h co-culture, while after 24-h co-culture TADM was no more detectable, suggesting cleavage of the acetyl groups in vitro. The Type 1 immune response enhancing effects of TADM and other, stereochemically and structurally similar, trivalent acetylated glycoclusters may be due to transmembrane uptake of macrophages independent of the mannose receptor.